Technologies to Support the Technical Debt Management in Software Projects: A Qualitative Research - Silva, Victor; Travassos, Guilherme Horta (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
Technical debt (TD) is a still incipient subject adopted by software practitioners, despite being an increasing interest topic among researchers. This work aimed to produce a summary of the central concepts related to TD, including the software technologies currently available to manage it. A survey with practitioners from Brazilian software organizations (BSOs) was conducted to assess the knowledge level on TD, including the technologies adopted by the software practitioners in the industry. Following this study, a quasi-systematic literature review was undertaken to gather specific technologies to manage the TD. We observed indications that the general knowledge of the BSOs′ software practitioners regarding TD is low, and only a minority of the participants mentioned strategies to manage TD. Evidence briefings (EBs) synthesized the results from the studies. EBs are one-page documents intended to improve the knowledge transfer between the researchers and the practitioners from the industry. Besides, the characterization of TD and its management technologies in Brazilian Software Organizations, this dissertation also contributes to the distribution of a research package to aid in the studies replication process, containing the survey plan and its instruments. Moreover, the EBs can be used by the software practitioners, as an instrument to aid the inclusion of TD management practices in BSOs. This dissertation produced a paper discussing the survey research at CIbSE 2018, which received the best paper award at the ESELAW track, and an invitation to extend it on a JSERD paper, which is being under development. Another paper, with a general overview of the research conducted at the dissertation, was presented at the SBQS 2018.